Release of florfenicol in seawater using chitosan-based molecularly imprinted microspheres as drug carriers. (December 2021) - Li, Fang; Lian, Ziru; Song, Chunxia; Ge, Changzi
Abstract: Novel molecularly imprinted polymer (MIP) microspheres using functionalized chitosan as eco-friendly substrates were prepared by surface imprinting method and applied as drug delivery carriers to provide extended-release of florfenicol (FF) in seawater. The chitosan-based composites were characterized by scanning electron microscopy and Fourier transforms infrared spectroscopy analyses. The swelling behavior, adsorption capability, and selectivity for FF were investigated. The results show that the MIPs possessed high drug loading saturation capacity and specific recognition affinity for FF. The release studies of MIPs as drug delivery carriers were evaluated in natural seawater. The microspheres exhibited slow sustained release profiles of FF and the release behavior conformed to the first-order kinetic equation. The imprinted microspheres as drug delivery devices would be a promising application for improving the efficacy of the antibiotic without exposing the ecological system to excess FF in aquaculture. Graphical abstract: Unlabelled Image Highlights: Novel molecularly imprinted polymers for florfenicol (FF-MIPs) were prepared. The chitosan-based composites showed remarkable drug loading capacity. The MIPs were applied as eco-friendly drug delivery carriers of targeted FF. The MIPs exhibited a two-phase sustained release of FF in natural seawater.